2006
DOI: 10.1158/1055-9965.epi-04-0866
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Treatment Alters the Gene Expression Profile of Normal Colonic Mucosa

Abstract: A clinical trial was recently conducted to evaluate the safety and efficacy of a selective inhibitor of cyclooxygenase-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 75 publications
1
37
0
1
Order By: Relevance
“…In conclusion, the present clinical findings emphasized that prostanoid metabolism is complex in colon cancer tissue and involves several hundred genes, which appear to control local tumor growth and net immune response (20,42), cell proliferation, differentiation, energy metabolism and apoptosis as earlier reported for normal colon tissue (41). However, alterations in tumor tissue gene expression following indomethacin treatment were not entirely similar to alterations in normal colon tissue from the same patients or to findings in cultured colon cancer cell lines.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In conclusion, the present clinical findings emphasized that prostanoid metabolism is complex in colon cancer tissue and involves several hundred genes, which appear to control local tumor growth and net immune response (20,42), cell proliferation, differentiation, energy metabolism and apoptosis as earlier reported for normal colon tissue (41). However, alterations in tumor tissue gene expression following indomethacin treatment were not entirely similar to alterations in normal colon tissue from the same patients or to findings in cultured colon cancer cell lines.…”
Section: Discussionsupporting
confidence: 78%
“…Our purpose with gene profiling was to map appearance/disappearance of gene transcripts in relationship to high and low PGE 2 content in tumor tissue despite tumor stage, as earlier reported for normal colon tissue after longterm treatment with celecoxib (41). Similarly, an earlier report from our group displayed impacts on HLA antigen expression including markers for immune defense reactions (20), in agreement with a report by Auman et al who pretreated patients with celecoxib for 7 days and found evidence of increased immune response (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, differential proteomic and transcriptomic profiling in colorectal cancer cell lines and healthy colonic mucosa of patients with hereditary nonpolyposis colon cancer, respectively, have shown celecoxib-mediated expression changes in diverse cellular functions, including cell proliferation, apoptosis, immune function, and cell signaling (18,19). In this investigation, we have performed transcription profiling of colorectal cancer cells to gain an unbiased global perspective of molecular networks and pathways targeted by celecoxib.…”
Section: Introductionmentioning
confidence: 99%
“…GC-rich sequence DNA-binding factor (GCFC2) factor were found to be differentially expressed in celecoxib treated hereditary nonpolyposis colon cancer patient cells 187 . GCFC2 was also found to be down regulated after the treatment of ETC-1922159 in colorectal cancer cells 51 .…”
Section: Dicationmentioning
confidence: 99%